P-THER-06: Endoscopic ultrasound-guided drainage and sequential direct endoscopic necrosectomy for pancreatic fluid collection using a new biflanged metal stent - Tsuchiya, Takayoshi (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Endoscopic ultrasound-guided transluminal drainage (EUS-TD) and sequential direct endoscopic necrosectomy (DEN) for pancreatic fluid collections (PFCs) have been reported as a useful treatment. Recently, a new dedicated biflanged metal stent (BFMS) matched to the PFC condition has been developed. Herein, we show the prospectively evaluated clinical outcome of this new BFMS for the treatment of PFCs. METHODS: EUS-TD using new stent was performed in 17 patients for PFCs (4 pancreatic pseudocysts; 13 walled-off necrosis). When clinical resolution could not be achieved within a few days after EUS-TD, DEN was performed the following day. RESULTS: New stent was deployed successfully with a median procedure time of 16 min and with no procedure-related adverse events in all the patients. DEN (n = 5) and/or additional drainage procedure (n = 6) through the stent were achieved in all the patients in whom they were attempted (8/8). Stent dislocation during DEN was not observed in any patients, but in one patient, spontaneous stent migration was observed. Two WON patients died from pseudoaneurysm rupture occurring between the endoscopic necrosectomy sessions and from multiple organ failure although hemostasis was achieved by coil embolization. The PFCs in the other 15 patients completely resolved. CONCLUSIONS: The new BFMS is technically feasible and safe for the treatment of PFCs.